Adjuvant Versus Early Salvage Radiation Therapy After Radical Prostatectomy for pN1 Prostate Cancer and the Risk of Death. Issue 20 (10th July 2022) - Tilki, Derya; Chen, Ming-Hui; Wu, Jing; Huland, Hartwig; Graefen, Markus; D'Amico, Anthony V.
Abstract : PURPOSE: An association with a reduction in the risk of all-cause mortality (ACM) and the use of adjuvant as compared with early postradical prostatectomy salvage radiation therapy (sRT) in men with pN1 prostate cancer (PC) has been observed. Yet, whether this finding applies irrespective of the number of positive lymph nodes (LNs) after adjusting for the time-dependent use and duration of androgen deprivation therapy is unknown and is addressed in the current study. METHODS: Univariable and multivariable Cox regression was used to evaluate whether the ACM risk ratio for time-dependent use of adjuvant versus early sRT per unit increase in positive pelvic LNs was significantly reduced. Adjusted ACM estimates were calculated among men who received adjuvant, early salvage, or no RT stratified by one to three or four or more positive pelvic LNs. RESULTS: After a median follow-up of 7.02 years, 986 (5.50%) men died, with 223 (22.62%) of PC. Adjuvant compared with early sRT was associated with a significantly lower ACM risk per unit increase in positive pelvic LNs (adjusted hazard ratio: 0.92; 95% CI, 0.85 to 0.99; P = .03). A significant difference in the 7-year adjusted ACM estimates favoring aRT versus early sRT was observed in men with four or more positive LNs (7.74% v 23.36%) in that the 95% CI for the 15.62% difference (5.90 to 25.35) excluded 0.00, but this was not true for men with 1-3 positive LNs (14.27% v 13.89%; 95% CI for the 0.38% difference [–7.02 to 7.79]). CONCLUSION: Adjuvant compared with early sRT in men with pN1 PC was associated with a decreased ACM risk, and this reduction increased with each additional positive pelvic LN. Abstract : In men with pN1 PC, adjuvant RT use was associated with a significant reduction in the risk of death compared with early sRT